Mosaic tetrasomy 9p at amniocentesis in a pregnancy associated with a favorable fetal outcome, perinatal progressive decrease of the aneuploid cell line and cytogenetic discrepancy in various tissues - Chih-Ping Chen; Shin-Wen Chen; Schu-Rern Chern; Peih-Shan Wu; Fang-Tzu Wu; Yen-Ting Pan; Chen-Chi Lee; Chen-Wen Pan; Yun-Yi Chen; Wayseen Wang (Elsevier, 2023)
Objective: We present mosaic tetrasomy 9p at amniocentesis in a pregnancy associated with a favorable fetal outcome, perinatal progressive decrease of the aneuploid cell line and cytogenetic discrepancy in various tissue. Case report: A 33-year-old primigravid woman underwent elective amniocentesis at 18 weeks of gestation because of anxiety, and the karyotype of cultured amniocytes was 47,XX,+i (9) (p10)[20]/46,XX [55]. Cordocentesis was performed at 20 weeks of gestation, and the karyotype of cord blood was 47,XX,+i (9) (p10)[7]/46,XX [15]. She was referred for genetic counseling at 23 weeks of gestation, and repeat amniocentesis revealed a karyotype of 47,XX,+i (9) (p10)[1]/46,XX [16] with seven cells in one colony having tetrasomy 9p in cultured amniocytes, and in uncultured amniocytes, quantitative fluorescence polymerase chain reaction (QF-PCR) analysis excluded uniparental disomy (UPD) 9 and determined paternal origin of the extra i (9p), array comparative genomic hybridization (aCGH) analysis on the DNA extracted from uncultured amniocytes revealed arr 9p24.3p13.1 × 3.0 consistent with 50% mosaicism for tetrasomy 9p, and interphase fluorescence in situ hybridization (FISH) on uncultured amniocytes showed 22.6% (12/53 cells) mosaicism for tetrasomy 9p. A third amniocentesis at 27 weeks of gestation revealed a karyotype of 46, XX (10/10 colonies) in cultured amniocytes, and interphase FISH analysis on uncultured amniocytes revealed 20% (20/100 cells) mosaicism for tetrasomy 9p. The parental karyotypes and prenatal ultrasound were normal. At 39 weeks of gestation, a phenotypically normal 3388-g female baby was delivered. The karyotypes of cord blood, umbilical cord and placenta were 47,XX,+idic (9) (q12)[19]/46,XX [21] or 47,XX,+idic (9) (pter→q12:q12→pter)[19]/46,XX [21], 47,XX,+idic (9) (q12)[1]/46,XX [39] and 47,XX,+idic (9) (q12)[4]/46,XX [36], respectively. When follow-up at age two months, the neonate was phenotypically normal, the peripheral blood had a karyotype of 47,XX,+idic (9) (q12)[18]/46,XX [22], and interphase FISH analysis on 100 buccal mucosal cells revealed 1% (1/100 cells) mosaicism for tetrasomy 9p. When follow-up at age seven months, the neonate was phenotypically normal, and the peripheral blood had a karyotype of 47,XX,+idic(9)(q12)[14]/46,XX[26]. Conclusion: Mosaic tetrasomy 9p at amniocentesis can be a transient and benign condition, and can be associated with a favorable fetal outcome and perinatal progressive decrease of the aneuploid cell line and cytogenetic discrepancy in various tissue.